Exploring predictors of HIV-1 virologic failure to long-acting cabotegravir and rilpivirine: a multivariable analysis. (15th July 2021) - Cutrell, Amy G.; Schapiro, Jonathan M.; Perno, Carlo F.; Kuritzkes, Daniel R.; Quercia, Romina; Patel, Parul; Polli, Joseph W.; Dorey, David; Wang, Yongwei; Wu, Sterling; Van Eygen, Veerle; Crauwels, Herta; et al.
Abstract : Objective: Efficacy and safety of long-acting cabotegravir (CAB) and rilpivirine (RPV) dosed intramuscularly every 4 or 8 weeks has been demonstrated in three Phase 3 trials. Here, factors associated with virologic failure at Week 48 were evaluated post hoc . Design and methods: Data from 1039 adults naive to long-acting CAB+RPV were pooled in a multivariable analysis to examine the influence of baseline viral and participant factors, dosing regimen and drug concentrations on confirmed virologic failure (CVF) occurrence using a logistic regression model. In a separate model, baseline factors statistically associated with CVF were further evaluated to understand CVF risk when present alone or in combination. Results: Overall, 1.25% ( n = 13/1039) of participants experienced CVF. Proviral RPV resistance-associated mutations (RAMs), HIV-1 subtype A6/A1, higher BMI (associated with Week 8 CAB trough concentration) and lower Week 8 RPV trough concentrations were significantly associated ( P < 0.05) with increased odds of CVF (all except RPV trough are knowable at baseline). Few participants (0.4%) with zero or one baseline factor had CVF. Only a combination of at least two baseline factors (observed in 3.4%; n = 35/1039) was associated with increased CVF risk (25.7%, n = 9/35). Conclusion: CVF is an infrequent multifactorial event, with a rate of approximately 1% in the long-acting CAB+RPV arms across Phase 3 studies (FLAIR, ATLAS and ATLAS-2M) through Week 48. Presence of at least two of proviral RPV RAMs, HIV-1 subtype A6/A1 and/or BMI at least 30 kg/m 2 was associated with increased CVF risk. These findings support the use of long-acting CAB+RPV in routine clinical practice. Abstract : Supplemental Digital Content is available in the text